Legal Manuscript: A Juridical Analysis of Informed Consent in Surgical Procedures - E.Supriadi; F.Rachman (International Medical Journal Corp. Ltd, 2025)
Introduction: Informed consent serves as the cornerstone of medical law, balancing patient autonomy against the complexities of surgical interventions. In surgical practices, where risks are inherently high, the legal validity of consent is frequently challenged due to informational asymmetry between physicians and patients. This study examines the legal construction of informed consent under Indonesian medical law and evaluates the criteria for its validity in high-risk surgical procedures. Methods: This study employs a normative juridical research method. It analyzes secondary data, including statutory legislation, judicial precedents, and legal literature related to healthcare, medical practices, and patient rights. Results: The findings indicate that while statutory provisions explicitly mandate comprehensive disclosure, the practical implementation often reduces informed consent to a mere administrative formality. Legal vulnerabilities arise when disclosures lack clarity regarding alternative treatments, specific surgical failure rates, and long-term postoperative risks. Discussion: The discussion highlights a significant research gap concerning the lack of standardization in delivering risk information, which compromises the legal protection of both patients and medical practitioners. A detailed literature review reveals that under the Civil Code and Medical Practice Act, valid consent must fulfill the criteria of voluntariness, capacity, and comprehensive disclosure. In surgical contexts, incomplete disclosure constitutes a breach of professional duty, transforming an authorized medical act into an unlawful act (onrechtmatige daad). Conclusions: In conclusion, informed consent in surgical procedures must transcend administrative compliance to ensure genuine autonomous decision-making. The study recommends the implementation of standardized digital disclosure protocols and legislative amendments to provide clearer boundaries for emergency exceptions, thereby enhancing legal certainty and safeguarding patient autonomy.